Clinical characteristics and outcomes of COVID-19 hospitalized patients with diabetes in the United Kingdom: A retrospective single centre study. (July 2020) - Alkundi, Alamin; Mahmoud, Ibrahim; Musa, Abdelmajid; Naveed, Saima; Alshawwaf, Mohammed
Abstract: Aim: To describe the clinical characteristics and outcomes of hospitalized COVID-19 patients with diabetes. Methods: A retrospective cross-sectional study was conducted among patients admitted to the William Harvey Hospital in England between March 10th and May10th, 2020 with a laboratory-confirmed severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2), known as COVID-19. Variation in characteristics, length of stay in hospital, diabetes status, duration of diabetes, control of diabetes, comorbidities and outcomes were examined. Results: There were 232 COVID-19 presentations. Mean (standard deviation (SD), range) age was 70.5 (±15.7, 30–101) years, 62.5% were male, and 37.5% were having diabetes. There were 43.4% males and 27.6 females, p = 0.016, with diabetes admitted to our hospital due to COVID-19. Patients with diabetes were more likely to have longer length of stay (LOS) in hospital, 14.4 (SD ± 9.6) days, compared to the patients without diabetes, 9.8 (SD ± 17.1) days, p < 0.0001. Patients with diabetic ketoacidosis (DKA) were more likely to survive (87.1%) compared to patients without DKA (50.6%), p = 0.046. Conclusion: Males were more likely to be admitted to hospital with COVID-19 illness than females. Hospitalized COVID-19 patients with diabetes had a longer LOS in hospital than patients without diabetes. Older age COVID-19 patients with diabetes and patients without DKA were less likely to survive compared to younger patients and patients with DKA, respectively. Further studies with large sample size are needed.